2021
DOI: 10.1084/jem.20191593
|View full text |Cite
|
Sign up to set email alerts
|

The pleiotropic roles of leptin in metabolism, immunity, and cancer

Abstract: The discovery of the archetypal adipocytokine leptin and how it regulates energy homeostasis have represented breakthroughs in our understanding of the endocrine function of the adipose tissue and the biological determinants of human obesity. Investigations on leptin have also been instrumental in identifying physio-pathological connections between metabolic regulation and multiple immunological functions. For example, the description of the promoting activities of leptin on inflammation and cell proliferation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
49
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 245 publications
(271 reference statements)
3
49
0
1
Order By: Relevance
“…Concomitantly, JAK2 phosphorylates insulin receptor substrates 1 and 2 (IRS1 and 2), causing the downstream activation of forkhead box protein O1 (FOXO1) and mammalian target of rapamycin (mTOR). The activation of the mTOR pathway by leptin is responsible for the activation of POMC neurons and for the peripheric effects of leptin in leukocytes (47)(48)(49). FOXO1 also promotes POMC transcription and AgRP/NPY inhibition (38,50).…”
Section: The Hypothalamic Region and Leptin Signaling Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…Concomitantly, JAK2 phosphorylates insulin receptor substrates 1 and 2 (IRS1 and 2), causing the downstream activation of forkhead box protein O1 (FOXO1) and mammalian target of rapamycin (mTOR). The activation of the mTOR pathway by leptin is responsible for the activation of POMC neurons and for the peripheric effects of leptin in leukocytes (47)(48)(49). FOXO1 also promotes POMC transcription and AgRP/NPY inhibition (38,50).…”
Section: The Hypothalamic Region and Leptin Signaling Pathwaymentioning
confidence: 99%
“…Individuals carrying only one functional copy of LEP exhibit diminished/undetectable serum leptin levels and show normal birthweight followed by rapid weight gain, hyperphagia, hyperinsulinemia, development of type 2 diabetes mellitus, sympathetic system dysfunction, and hypothalamic pituitary gonadal axis dysfunction (23,(61)(62)(63). Leptin is also known to be important for the modulation of inflammatory responses (49). Leptin deficiency is related to reduced serine protease inhibitor a1-antitrypsin (A1AT) expression, a neutrophil elastase (NE) inhibitor that protects tissue from inflammatory damage.…”
Section: Congenital Leptin Deficiencymentioning
confidence: 99%
“…Leptin adipocytokine is a pleiotropic hormone involved into widespread physiologic function, such as appetite and metabolic rate ( Münzberg and Morrison, 2015 ; Mancuso et al, 2018 ), and in maintaining the homeostasis of immune system ( La Cava and Matarese, 2004 ; Pérez-Pérez et al, 2017 ; Maurya et al, 2018 ; de Candia et al, 2021 ; Salum et al, 2021 ). The lung has been known as a sensitive and leptin-producing organ for more than 20 years with extensive research published for the role of leptin in the respiratory system, both in animals ( Wang et al, 1996 ; De Matteis et al, 1998 ; Tsuchiya et al, 1999 ; Bergen et al, 2002 ) and humans ( Bruno et al, 2005a , 2009 , 2011 ; Unal et al, 2006 ; Vernooy et al, 2009 ; Malli et al, 2010 ; Brandao-Rangel et al, 2021 ; Figure 1A ).…”
Section: Introductionmentioning
confidence: 99%
“…Leptin is a 16-kDa multifunctional, neuroendocrine peptide hormone secreted by adipocytes in proportion to total adipose tissue mass, known to control food intake, energy homeostasis, immune response, and reproductive processes. A growing body of evidence has highlighted that this adipokine, through the binding of its own receptor (ObR) and crosstalk with other pathways (i.e., estrogen, growth factor, and inflammatory cytokine signaling), impacts multiple hallmarks of cancer, including survival, metabolic rewiring, angiogenesis, invasion, and metastasis [ 1 , 2 , 3 , 4 ]. Indeed, it has been widely demonstrated that leptin, mainly produced by distant and local adipocytes but also by epithelial tumor cells itself and other cells within the tumor microenvironment (i.e., cancer-associated fibroblasts), is able to affect different aspects of cancer biology in an endocrine, paracrine, and autocrine manner.…”
mentioning
confidence: 99%
“…Indeed, it has been widely demonstrated that leptin, mainly produced by distant and local adipocytes but also by epithelial tumor cells itself and other cells within the tumor microenvironment (i.e., cancer-associated fibroblasts), is able to affect different aspects of cancer biology in an endocrine, paracrine, and autocrine manner. Accordingly, both clinical and experimental data have indicated the involvement of leptin/ObR axis in the promotion of tumor development and progression, as well as reduction in the efficacy of cancer treatments [ 1 , 2 , 3 , 4 ]. Importantly, among adipokines, leptin has been widely recognized as a key driver of the complex network that exists between cancer and obesity, a worldwide recognized health problem [ 5 , 6 , 7 , 8 , 9 ].…”
mentioning
confidence: 99%